P087 Communicating Needs and Features of IBD Experiences (CONFIDE) Survey: Impact of Ulcerative Colitis Symptoms on Daily Life. (21st January 2022) - Dubinsky, M C; Schreiber, S; Potts Bleakman, A; Kayhan, C; Ellis, H; Hunter Gibble, T; Flynn, E; Suldecki, G; Travis, S
Abstract: Background: Bowel urgency is the symptom described by patients as having the most impact on quality of life but is missing from most disease activity indices (Carpio et al., 2016). The Communicating Needs and Features of IBD Experiences (CONFIDE) study aims to increase understanding of patients' experiences and the impact of IBD on their lives in the United States (US), Europe, and Japan. These data focus on US patients with moderately-to-severely active ulcerative colitis (UC). Methods: An online, quantitative, cross-sectional survey was conducted with patients with moderately-to-severely active UC in the US in July 2021. Data included patient perspectives on their UC symptoms and the impact on their social life, work/school life, and ability to participate in sports/physical activities. Moderately-to-severely active UC was defined based on treatment, steroid use, and/or hospitalization history. Descriptive statistics (frequencies, percentages) summarise the data. Results: 200 (of 756 total contacted) patients (61.5% male, mean age 40.4, mean disease duration 7.9 years) completed the survey in the US, with 77% (n=153) of patients receiving advanced therapies (biologic or novel oral therapy). Patients declined participation in social events due to bowel urgency (43%), fear of urge incontinence (40%), increased stool frequency (29%), and blood in stool (15%) in the last three months (Fig. 1). Patients declined participation in sports/physical exercise due to bowel urgency (38%), fear of urge incontinence (36%), increased stool frequency (24%), and blood in stool (10%) in the last three months (Fig. 2). Patients declined participation in work/school due to bowel urgency (37%), fear of urge incontinence (42%), increased stool frequency (25%), and blood in stool (16%) in the last three months (Fig. 3). Out of 123 patients who have ever suffered from bowel urgency, in the last three months 42% stopped working for the day sooner than planned and 41% worked fewer hours. Notably, 76% of patients reported wearing a diaper/pad/protection at least once in the last three months due to fear of urge incontinence. Bowel urgency had no impact on work/school for 22% (n=27) of patients who had ever experienced bowel urgency (Fig. 4). Conclusion: Bowel urgency and fear of urge incontinence are the most reported symptoms leading to patients with UC declining participation in work/school, social events, and sports/physical exercise. Over three quarters of the surveyed patients reported wearing diapers/pads/protection in the past three months due to fear of urge incontinence and only 22% of patients who had ever suffered from bowel urgency reported that it had no impact on work or school.